Beyond the AI Model Race – How Open Ecosystems Are Redefining the Future of Platform Competition - Putu Basya Ratu Sanceska (Journal of Business, Management, and Social Studies, 2026)
This commentary examines the rise of DeepSeek and the transformation of generative artificial intelligence competition from a technological race into a platform ecosystem competition. Using platform ecosystem theories, including network effects, innovation platforms, API strategies, ecosystem governance and value co-creation, this article analyzes how AI companies create competitive advantages by enabling collaboration between developers, businesses and users. The discussion highlights that long - term success in artificial intelligence depends not only on technological capabilities but also on the ability to orchestrate sustainable and trusted digital ecosystems.